(untitled) (Bangladesh Heart Journal, 2021)
Stent thrombosis is one of the gravest complications of percutaneous coronary intervention which usually manifest as ST-segment elevation myocardial infarction or sudden death. There are a very few case reports in the literature regarding extremely late stent thrombosis in a drug-eluting stent. Here we report a case of extremely late stent thrombosis in a first generation drug-eluting stent in a 54 year old gentleman. To the best of our knowledge, this is the first case report with the longest duration (10 years) after sirolimus eluting first-generation DES in Bangladesh. Bangladesh Heart Journal 2021; 36(2): 164-168